Strategic drivers and business model innovation in cloud-based BIM - Odubiyi, Tawakalitu; Hafez, Mohamed; Wan Voon, Betty (Frontiers in Built Environment, 2026)
Building Information Modelling (BIM) is driving transformation in the built environment. While technical aspects have been widely explored, less is known about how cloud-based BIM (CBIM) supports business strategy and growth. This gap poses a challenge for organisations aiming to integrate digital innovation with competitive advantage. This study develops a CBIM business model framework, identifying strategic drivers for business expansion. Unlike prior BMC adaptations, the proposed framework integrates both microeconomic dimensions (e.g., pricing logic, competition, diversification) and macroeconomic dimensions (e.g., governance, sustainability, reskilling), explicitly linking firm-level strategies with broader institutional and digital infrastructure factors. A qualitative multi-case study was conducted, involving nine semi-structured interviews with CBIM experts across Germany, Finland, the Netherlands, and the UK. Participants represented both BIM consumers (e.g., construction companies and consultants) and BIM producers (e.g., software vendors and platform providers). Purposeful sampling ensured sectoral and role diversity. Data was coded and analysed thematically using Atlas. ti qualitative analysis software. The study identifies nine strategic drivers for CBIM business growth, including a redefined value proposition, customer awareness, cloud infrastructure, product and service pricing logic, distribution channels, human resource capabilities, strategic use of competition, diversification, governance and sustainability. The study proposes a CBIM-adapted Business Model Canvas framework, providing actionable insights for startups and SMEs, including guidance on integrating cloud pricing models and aligning internal capabilities with digital strategy such as guidance on integrating cloud pricing models and aligning internal capabilities with digital strategy, while also highlighting strategies that incumbents can adopt to maintain competitiveness in a rapidly digitising construction ecosystem.